Religion, Immigration, and the Role of Context: The Impact of Immigration on Religiosity in the Republic of Cyprus - Kouros, Theodoros; Papadakis, Yiannis (My University, 2018)
This article examines the impact of immigration on the religiosity of four immigrant groups in the Republic of Cyprus. It attempts to shed light on the various factors that impact the religiosity of immigrants in Cyprus and on whether migration has a theologizing or alienating effect, i.e., whether it affects the religiosity of immigrants positively or negatively. It concludes that immigrants’ religious identities are being negotiated and transformed largely by their interplay with the local population, thus moving the focus beyond the theologizing/alienating dichotomy and beyond the religion as a bridge or barrier debate.
Keywords: religion; immigration; Cyprus; immigrant religiosity; theologizing hypothesis; bridge; barrier